Facem un artificiu de calcul :
[tex]3 * 19^n +11^{n+1}+19* 8^n = 3 *19^n +11^n * 11+19 * 8^n=\\3 * 19^n +11^n * (9+2)+(21-2) * 8^ n =3*19^n+9\\3*19^n+9*11^n+2*11^n+21*8^n-2*8^n =\\ \\3*(19^n+3*11^n+7*8^n) +2*(11^n-8^n)=\\Sa~ observam~ ca~ 3*(19^n+3*11^n+7*8^n)~ este~ multiplu~ de~ 3.\\Ramane~ sa~ aratam~ ca~ si~ 2*(11^n-8^n)~ este~ multiplu~ de~ 3.\\Dar~ stim~ urmatoarea~ identitate~ a^n-b^n~ \vdots~ a-b,\forall n\in N^*,deci \\11^n-8^n~ \vdots~ 11-8 = 3,deci~ am~ aratat~ ca~ toata~ expresia~ este~ multiplu\\de~ 3.[/tex]